2020
DOI: 10.31557/apjcp.2020.21.4.1057
|View full text |Cite
|
Sign up to set email alerts
|

Incidence, Clinico-demographic Profiles and Survival Rates of Colorectal Cancer in Northern Malaysia: Comparing Patients Above and Below 50 Years of Age

Abstract: Colorectal cancer (CRC) is the third most common cancer in men and the second in women worldwide. In 2018, the World Health Organization reported nearly 1.85 million new CRC cases and 0.88 million CRC-related deaths (Wong et al., 2019). Malaysia, together with China, Japan, Korea and Singapore, has recorded the highest 5-year prevalence of CRC (≥46.5 cases in 100,000) in Asia (Haggar and Boushey, 2009). It is well known that the prognosis of a CRC patient is strongly related to the stage at which the cancer is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 20 publications
2
24
0
Order By: Relevance
“…Table 1 summarizes the basic information on these studies. Data for nine studies 16,20,36,37,39–42,45 were obtained from national/state databases or tumor registries ( n = 443,997), and data for four 35,38,43,44 were obtained from tertiary care centers ( n = 4784). The included studies were published from 2012 to 2022; two studies 40,45 only included colon cancer cases, and rectal cancer cases were only included in one study 16 .…”
Section: Resultsmentioning
confidence: 99%
“…Table 1 summarizes the basic information on these studies. Data for nine studies 16,20,36,37,39–42,45 were obtained from national/state databases or tumor registries ( n = 443,997), and data for four 35,38,43,44 were obtained from tertiary care centers ( n = 4784). The included studies were published from 2012 to 2022; two studies 40,45 only included colon cancer cases, and rectal cancer cases were only included in one study 16 .…”
Section: Resultsmentioning
confidence: 99%
“…Models that were reported only once in the reviewed literature included: time-series analysis ( 144 ), interrupted time-series analysis ( 83 ), bayesian analysis of spatio-temporal conditional autoregressive models ( 142 ), and the LOESS method ( 66 ). Six studies reported the APC without explaining the used model to derive this estimate ( 31 , 35 , 39 , 121 , 145 , 159 ).…”
Section: Resultsmentioning
confidence: 99%
“…Study of Leong et al (18) showed that the 5-year survival rate of older patients (≥70) was the worst compared with other ages. However, in some studies, there was no significant difference in mortality among different age groups of CRC patients (19). The reasons may be that: (I) with the improvement of medical level, the survival rate of elderly patients with CRC has improved; (II) the cancer of young patients is more aggressive and less responsive to treatment; and (III) ethnicity is an important predictor for survival of CRC patients (18).…”
Section: Discussionmentioning
confidence: 99%